Antibacterial activity of secondary metabolites isolated from Ficus aurata (Miq.) Fruits - Nurhamidah Nurhamidah; M Lutfi Firdaus; Suryati Suryati; Yosie Andriani (Current Research on Bioscences and Biotechnology, 2021)
This research aimed to isolate chemical constituents from ethyl acetate and n-hexane fractions of Ficus aurata (Miq.) fruits and investigated their antibacterial activity. Chemical constituents were separated using vacuum liquid chromatography, gravity column chromatography, and thin-layer chromatography. The structures of the isolated compounds 3,4-dihydroxybenzoic acid (1) and β-sitosterol (2) were elucidated using various spectroscopic methods, including UV, IR, and NMR (1H-NMR, 13C-NMR, and DEPT). While, antibacterial activity was done using resazurin microtiter assay. These 2 compounds were first time reported from F. aurata fruit. In addition, analysis of the bioassay showed that compound 1 had a notable antibacterial activity against Gram negative (Escherichia coli ATCC 25922 and Pseudomonas aeruginosa ATTC 27853), and a gram-positive bacterium (Staphylococcus aureus ATCC 23235) with the minimum inhibitory concentration (MIC) value of 0.1563 µg/ml, and it indicated the same MIC as cefadroxil (positive control). Compound 2 has weak antibacterial activity compared to cefadroxil (positive control). The results found that F. aurata (Miq.) fruits metabolites have antibacterial activity and show potency as antibacterial agents. Different kinds of bacteria and assay could be needed to investigate and support its antibacterial activity in the future.